Beta-Glucan and Phenolic Compounds: Their Concentration and Behavior during in Vitro Gastrointestinal Digestion and Colonic Fermentation of Different Barley-Based Food Products - Mosse, Juana Inés (2018)
Among cereals, barley (Hordeum vulgare L.) is notable for its high content of bioactives such as β-glucan and phenolic compounds, but it is not used as widely in human nutrition as wheat. To compare the impact of food formulation and processing on barley bioactives, crackers, cookies, and fresh pasta were prepared combining wheat and barley flour. After quantification of β-glucan and PCs in the barley flour and barley-based products, their behavior during in vitro gastrointestinal digestion and colonic fermentation was studied. The β-glucan and PCs were not drastically affected by processing. The amount of bioaccessible compounds after gastrointestinal digestion was lower than the amount retained in the undigested fraction. After in vitro colonic fermentation, β-glucan was mainly metabolized to acetic and propionic acids and PCs to phenylpropionic and phenylacetic acids. Based on the results of the study, the daily ingestion of barley-based foods may contribute to the intake of beneficial bioactive compounds.